Ta’stīru Wasāili Ta’līmi Alīf Īdūkātiyūn ‘ala al-Annatāiji al-Dirāsiyati liṭalabati al-Lughati al-‘Arabiyyati fī al-Ṣaffi al-Stāmani fī al-Madrasti al-Stanuwiyyati al-Hukūmiyyati 1 Dīlī Sirdang: Universitas Islam Negeri Sumatera Utara Medan, Indonesia - Naufal, Imam; Yulia, Fatma (Al-Uslub: Journal of Arabic Linguistic and Literature, 2024)
The purpose of this study was to test the influence of the Alef Education platform on the learning outcomes of Arabic language students in class VIII at MTsN 1 Deli Serdang. The research method used in this study is to use a quantitative research method with experimental techniques by comparing student learning outcomes. After the researcher conducted research and experiments on class VIII students at MTsN 1 Deli Serdang, the researcher found that the Alef Education platform greatly influenced student learning outcomes because of better results when using the Alef Education platform and students were also more active in the learning process. In addition, the advantages of the Alef Education platform are also that the lesson cards are very easy for students to digest.